A New Catalytic Site for the Electroreduction of Oxygen?. Issue 7 (27th May 2014) - Dodelet, Jean‐Pol; Chenitz, Régis; Yang, Lijun; Lefèvre, Michel
<x xml:space="preserve">Abstract</x> The possibility of a new iron‐based catalytic site for the oxygen reduction reaction, comprising outer graphitic layers encasing a Fe3C core, is discussed in the context of iron‐based catalysts for proton‐exchange membrane fuel cells. Further analysis of new Fe3C‐700 and S2‐700 catalysts is still needed to determine the relationship between the active sites and oxygen reduction activity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>